Optimization of Traditional Jamu Utilization in Health Services at Terminal Purabaya by DPC ASPETRI Sidoarjo - Wibowo, Teguh Setiawan; Larasaty, Hartaty; Priyono, Khairul Bahri (Jurnal Pengabdian West Science, 2025)
Traditional herbal medicine has long been a part of Indonesia's health culture. Its use as a natural health drink is becoming increasingly relevant amid growing public awareness of a healthy lifestyle. To support the health of homecoming travelers undertaking long journeys during the Eid exodus, the Branch Leadership Council of the Indonesian Traditional Herbal Practitioners Association (DPC ASPETRI) of Sidoarjo Regency initiated a community service program through the distribution of immune-boosting herbal drinks at Purabaya Terminal. The herbal drink distributed was Jamu Waruga from CV Sangkuriang, containing ginger, moringa, gotu kola, and turmeric—herbs known for their benefits in boosting stamina and maintaining immunity. This activity aimed to optimize the use of traditional herbal medicine in health services by providing the public with direct access to high-quality herbal drinks. In addition to distributing the herbal drinks, the public was given brief education on the benefits of jamu and the importance of maintaining immunity during travel. The results of this activity showed a positive response from the community, who experienced direct benefits from consuming jamu and gained a better understanding of the efficacy of traditional herbal medicine. This initiative is expected to inspire further utilization of Nusantara’s herbal potential as part of a broader preventive health system.